New findings from conflict archives: An introduction and methodological framework. (March 2018) - Balcells, Laia; Sullivan, Christopher M
As they pursue information and deploy violence during conflict, combatants compose, catalog, and preserve a wide variety of records, such as memos, investigative reports, and communiqués. In an increasing number of post-conflict scenarios, these records are being archived and released publicly, quickly becoming a critical new source of data for studies of peace and conflict. The objective of this special issue is to advance a new research agenda focused on the systematic analysis of conflict archives. The contributors each spent significant time collecting original data from often-dusty archives and, in many cases, developed new methodologies for sampling, cataloging, and analyzing historical documents. Their findings reveal how violence simultaneously shapes and is shaped by factors that remain largely unobservable using more conventional sources of conflict data, including clandestine mobilization, bureaucratic accountability, and political identities. By considering these studies in relation to one another, this introduction aims to provide readers with a comprehensive understanding of field research strategies and analytical techniques for studying original data from conflict archives. We conclude that while archival data are subject to their own biases that must be considered, this research agenda addresses significant limitations associated with traditional data sources and, in turn, pushes scholars to rethink many of the mechanisms underlying the causes and dynamics of peace and conflict.